Economical viability and social acceptability of rainwater harvesting in households in the city of João Pessoa - Athayde Júnior, Gilson Barbosa (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The economic feasibility and social acceptability of rainwater harvesting in households in the city of João Pessoa, state of Paraíba, northeastern Brazil, were studied. Three social-economical household standards (low, middle, and high-class) were considered. Based on the existing water tax scenario, rainwater harvesting is unfeasible for low- and middle-class households. However, for the high socio-economical standard, it is economically feasible, with a current net present value varying between R$1.278.17 and R$ 2.254.00; a benefit/cost ratio of 1.30 to 1.47, and a payback period of 8.17 to 10.19 years. In order to learn about population acceptability, 800 interviews were applied. Results indicated that 66.1% of population of João Pessoa are aware of rainwater use in households, out of which, 54.37% effectively use it, despite infrequently. Including those who would use rainwater in their households, if they knew that this alternative was available, the potential use of rainwater would increase to almost two thirds of the population.